USING ATORVASTATIN AND L-CARNITINE IN PREVENTION OF PILOCARPINE-INDUCED SEIZURES: ANIMAL MODEL STUDY (Iraqi Journal of Medical Sciences, 2016)
Background:Epilepsy is a common chronic neurological disorder characterized by recurrent unprovoked seizures.Objective:To investigate the possible antiepileptic effect of both atorvastatin and L-carnitine on seizure induced by pilocarpine.Methods: Fifty male albino mice weighing between 30-35 gm were equally allocated into five groups (each group contained 10 mice) and were given one of the following; control group; distal water group (0.1 ml), diazepam group (1mg/kg), atorvastatin group (5 mg/kg) and L-carnitine group (300 mg/kg). All animals (except normal group) were injected with Pilocarpine hydrochloride (350 mg/kg) to induce generalized tonic-clonic seizures 30 minutes after the tested drugs had been administrated. The mean onset of seizure were determined as well as the mean serum concentration of electrolytes, glutathione (GSH) and malondialdehyde (MDA) were measured after seizure had been induced.Results: Pilocarpine induced seizure at approximately 7 minutes after injection, while both atorvastatin and L-carnitine produced highly significant increase in mean onset of seizure 14 ± 0.471 and 14.5 ± 0.909 respectively as compared to that of D.W. group, also both drugs produced highly significant changes in mean serum concentration of electrolytes, GSH and MDA.Conclusion: Atorvastatin and L-carnitine had antiepileptic effects against seizures induced by pilocarpine when used at applied doses.Key words:Epileptic seizure, Atorvastatin and L-carnitine.
Keywords: Epileptic seizure; Atorvastatin and Lcarnitine